1913 Minn. Gen. Laws 55, An Act to Prevent the Sale, Offering or Exposing for Sale or Having in Possession for the Use or for Purpose of Sale within this State, of Silencer for Shot-gun, Revolver, Rifle or Other Firearm, Defining a Silencer and Providing Penalties for Violation, ch. 64, §§ 1-4. - (:unkn) unknown (General Publisher, 1913)
Use of silencers prohibited. No person shall within the state of Minnesota sell or offer or expose for sale, or have in possession for use upon or in connection with any rifle, shot-gun, revolver, or other firearm or have in possession for purposes of sale any silencer for a shotgun, revolver, rifle or other fire-arm
--
Keywords: SUPPRESSORS